Impact of Nintedanib on tumor angiogenesis and vascular normalization in a mouse model of colorectal cancer - Naita M. Wirsik; Jens M. Seeger; Thomas Schmidt; Frank Hilberg; Hans F. Fuchs; Christiane J. Bruns; Oliver Coutelle; Hamid Kashkar; Lars M. Schiffmann (Discover Oncology)
Abstract Background For many solid types of cancer including colorectal cancer treatment with the VEGF antibody bevacizumab as anti-angiogenic treatment has become standard of care. Nevertheless, long-term treatment with anti-angiogenic drugs in combination with other treatment modalities or alone can induce resistance through alternative pro-angiogenic pathways. In this study, we investigated the effects of nintedanib, an anti- VEGFR/PDGFR/FGFR kinase inhibitor, on tumor vasculature to determine the potential benefits of combined inhibition of multiple pro-angiogenic factors. Methods In a colorectal xenograft model, subcutaneous tumors were treated with Nintedanib. Tumor growth patterns were measured and tumors were analysed histologically regarding effects on tumor angiogenesis and parameters of vascular normalization. Results Inhibition of VEGFR/PDGFR/FGFR by Nintedanib was able to reduce tumor growth by significantly inhibiting angiogenesis and inducing tumor cell death. The remaining vessels showed decreased vascular leakage and improved oxygen delivery, indicating a functionally and structurally improved vascular bed resulting from vascular normalization. Conclusion In xenograft mouse model of colorectal cancer Nintedanib revealed anti-tumoral effects and induced vascular normalization. Our findings indicate that the treatment with Nintedanib could be able to improve intratumoral oxygen and thereby drug delivery to potentially enhance the efficacy of preexisting oncological therapies such as chemotherapy and radiation.